Subclinical Pulmonary Hypertension in Childhood Systemic Lupus Erythematosus Associated with Minor Disease Manifestations - Anuardo, Pedro; Verdier, Monica; Gormezano, Natali W. S.; Ferreira, Gabriela R. V.; Leal, Gabriela N.; Lianza, Alessandro; Ferreira, Juliana C. O. A.; Pereira, Rosa M. R.; Aikawa, Nadia E.; Terreri, Maria Teresa; Magalhães, Claudia S. [UNESP]; Appenzeller, Simone; et al. (Springer Nature, 2017)
The aim of this study was to evaluate pulmonary hypertension (PH) in 852 childhood-onset systemic lupus erythematosus (cSLE) patients. This was a large multicenter study conducted in 10 Pediatric Rheumatology Services of São Paulo state, Brazil. PH was defined as systolic pulmonary artery pressure >35 mmHg and/or measurement of the mean pulmonary artery pressure >25 mmHg and/or diastolic pressure >15 mmHg by transthoracic echocardiogram. Demographic data, clinical manifestations, disease activity score (SLEDAI-2K), disease damage score (SLICC/ACR-DI) and treatments were also evaluated. Statistical analysis was performed using Bonferroni correction (p < 0.002). PH was observed in 17/852 (2%) cSLE patients. Effort dyspnea occurred in 3/17, chest pain in 1/17 and right ventricle dysfunction in 3/17 cSLE patients. None had pulmonary thromboembolism or antiphospholipid syndrome. Further comparison between 17 cSLE with PH and 85 cSLE control patients without PH with similar disease duration [15 (0–151) vs. 15 (0–153) months, p = 0.448], evaluated at the last visit, revealed higher frequencies of fever (47 vs. 9%, p < 0.001), reticuloendothelial manifestations (41 vs. 7%, p < 0.001) and serositis (35 vs. 5%, p = 0.001) in the former group. Frequencies of renal and neuropsychiatric involvements and antiphospholipid syndrome, as well as the median of SLEDAI-2K and SLICC/ACR-DI scores, were comparable in both groups (p > 0.002). Normal transthoracic echocardiography was evidenced in 9/17 (53%), with median cSLE duration of 17.5 months (1–40) after PH standard treatment. PH was a rare manifestation of cSLE occurring in the first two years of disease. The majority of patients were asymptomatic with mild lupus manifestations. The underlying mechanism seemed not to be related to pulmonary thromboembolism and/or antiphospholipid syndrome.
Keywords: Childhood systemic lupus erythematosus; Lung; Multicenter cohort; Pulmonary hypertension